Political cleavages in motion: Bolivia in 2021 - Gustavo Bonifaz Moreno; Jean-Paul Faguet (London School of Economics and Political Science (LSE), Department of International Development, 2022)
We analyze recent developments in Bolivia's politics through the lens of political cleavage theory, in particular cleavage displacement. Bolivia's current party system is characterized by a stable and dominant MAS at one end of the spectrum, and at the other a fractious, unstable collection of parties, movements, and other vehicles that have failed to articulate a coherent set of political ideas. It emerged when the previous party system collapsed in 2003-05, shifting politics from a conventional left-right axis of competition unsuited to Bolivian society, to an ethnic/rural vs. cosmopolitan/urban axis closely aligned with its major social cleavage. But society did not freeze in 2005. We analyze the deep roots of Bolivia's current politics, and explore emerging or changing generational, ethnic, urban-rural, regional, class, and religious divides. Understanding how cleavages interact to determine political outcomes allows us to make sense of the deep tensions and sources of instability that both Bolivia, and the MAS internally, currently face, and to shine a light on major coming challenges.
Keywords: 330; Cleavage theory; political parties; ethnicity; Bolivia; Latin America